Estimation of regional cerebral blood flow using N-isopropyl-p-123I iodoamphetamine acquisition data from the lungs and brain - Abe, S.; Kato, K.; Takahashi, Y.; Fujita, N.; Ikeda, M.; Ota, N.; Kajita, Y.; Yamamoto, S.; Naganawa, S. (Nuklearmedizin - NuclearMedicine, 2014)
Aim: Previously, we devised a method for estimating 123I labeled N-isopropyl-p-iodo- amphetamine (123I IMP) arterial blood activity at 10 minutes after intravenous injection of 123I IMP (Ca10) without any blood sampling using 123I IMP autoradiography (ARG) acquisition data, and verified its usefulness for quantification of regional cerebral blood flow (rCBF). In this study, we attempted to develop an improved noninvasive method for estimating rCBF. Patients, methods:123I IMP studies with 23 patients and 15O-H2O positron emission tomography (PET) ARG studies with 20 patients were evaluated. Multiple regression analysis was used to estimate an integral of the arterial blood counts during the time after injection of 123I (JCa) using parameters from the time series of the lung counts and brain counts as the explanatory variables and the fraction [brain single-photon emission computed tomography (SPECT) average count / the mean of rCBFs (mean CBF) measured by 15O-H2O PET ARG method] as the objective variable. Results: The regression equation was as follows: Estimated JCa = (7.09x10-3 · Cb12) - (1.57x10-4 · CbpreSPECT) + (9.48x10-5 · CbpostSPECT) + (1.35x10-4· L15) - (6.95x10-4· L33) + (7.61x10-4· L81) - (0.417), where Cb12: brain count at 12 minutes, Cbpre-SPECT: brain count before SPECT, Cbpost-SPECT: brain count after SPECT, L15, L33, and L81: lung count at 15, 33, and 81 seconds, respectively. The mean CBF values (ml/min/100g) calculated using the estimated JCa values more closely correlated with those measured by 15O-H2O PET ARG method (r = 0.833, p < 0.01) than those obtained by our previous method (r = 0.590, p < 0.01). Conclusion: The rCBFs obtained by this method approximated more accurately to the values measured by 15O-H2O PET ARG method than those obtained by our previous method.
Keywords: Cerebral blood flow; 123I IMP; 15O-H2O; SPECT; PET